Dietary intakes, nutritional and biochemical status of 6 months to 12-year-old children before the COVID-19 pandemic era: the South East Asian Nutrition Survey II Indonesia (SEANUTS II) study in Java and Sumatera Islands, Indonesia - Aria Kekalih; Dian Novita Chandra; Listya Tresnanti Mirtha; Ilse Khouw; Gerard Wong; Rini Sekartini (Public Health Nutrition, 2025)
Abstract